2015
DOI: 10.18632/oncotarget.3332
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib increases sensitivity to radiation in non-small cell lung cancer cells with acquired EGFR T790M mutation

Abstract: Afatinib is a second-generation of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor and has shown a significant clinical benefit in non-small cell lung cancer (NSCLC) patients with EGFR-activating mutations. However, the potential therapeutic effects of afatinib combining with other modalities, including ionizing radiation (IR), are not well understood. In this study, we developed a gefitinib-resistant cell subline (PC-9-GR) with a secondary EGFR mutation (T790M) from NSCLC PC-9 cells after ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…Low albumin concentrations in the CSF contribute to unbound afatinib as the primary form. As such, the PD analysis showed the EC 50 of afatinib was 0.26 nmol/L, a value similar to the in vitro IC 50 (0.28 nmol/L) of PC-9 cells reported in our previous work [20] . EGFR-TKIs are a class of small molecules that permeate across the BBB by two mechanisms: the lipophilic passive pathway and the receptor-mediated active transport pathway [21] .…”
Section: Wwwnaturecom/aps Zhang Sr Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…Low albumin concentrations in the CSF contribute to unbound afatinib as the primary form. As such, the PD analysis showed the EC 50 of afatinib was 0.26 nmol/L, a value similar to the in vitro IC 50 (0.28 nmol/L) of PC-9 cells reported in our previous work [20] . EGFR-TKIs are a class of small molecules that permeate across the BBB by two mechanisms: the lipophilic passive pathway and the receptor-mediated active transport pathway [21] .…”
Section: Wwwnaturecom/aps Zhang Sr Et Alsupporting
confidence: 89%
“…WBRT disrupts the BBB and leads to an increased passage of afatinib across the BBB via the passive pathway. Our previous work has shown that afatinib exhibits radiosensitization effects in PC-9 cells and PC-9 gefitinib-resistant cells with sensitization enhancement ratios (SERs) of 1.22 and 1.50, respectively [20] . Afatinib markedly blocked the basal level of EGFR and ERK phosphorylation and caused delays in the radiation-induced phosphorylation of AKT in lung cancer cells.…”
Section: Wwwnaturecom/aps Zhang Sr Et Almentioning
confidence: 99%
“…Of these cell lines, H1299 expresses wild-type EGFR, PC-9 expresses mutant EGFR with a 15-bp deletion (EGFR19Del), H1975 and PC-9-GR express mutant EGFRs with dual mutations, one of which includes T790M (EGFR-L858R/ T790M for H1975 and EGFR-19Del/T790M for PC-9-GR) [35] , and H460 expresses mutant KRAS (KRAS-Q61H). With IC 50 values determined by the MTS assay, we found that these cells responded to gefitinib treatment with a wide range of IC 50 values, but only PC-9 cells showed an IC 50 value at the nmol/L level (31.00±6.15 nmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…The human NSCLC cell line PC-9-GR was developed by chronic exposure to gefitinib as we previously reported [35] . All of the cell lines were maintained in RPMI-1640 (Gibco, Waltham, MA, USA) supplemented with 10% heat-inactivated fetal bovine serum (FBS) (Gibco, Waltham, Massachusetts, USA).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation